2020
DOI: 10.1590/0074-02760200009
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 infection and viral load analysis in patients with different clinical presentations

Abstract: BACKGROUND Influenza viral load (VL) can be a decisive factor in determining the antiviral efficacy in viral clearance. OBJECTIVE This study aimed to evaluate the rate of infection and the role of influenza VL on the clinical spectrum of illnesses among different patient groups attended at a tertiary hospital in Brazil. METHODS Samples were collected from patients presenting acute respiratory infection from 2009 to 2013. Overall, 2262 samples were analysed and distributed into three groups: (i) asymptomatic (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…Therefore, it is likely that these patients were already clearing the virus particularly that they were on antiviral therapy. These findings are consistent with previous studies showing that the highest influenza viral load is detected on day 0 of hospitalization in oseltamivir treated patients [ 67 , 68 ]. Our findings are also in line with studies done in college communities and multicentre areas, which revealed a negative association between the detection of aerosolized IAV and the time elapsed since illness onset [ 51 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is likely that these patients were already clearing the virus particularly that they were on antiviral therapy. These findings are consistent with previous studies showing that the highest influenza viral load is detected on day 0 of hospitalization in oseltamivir treated patients [ 67 , 68 ]. Our findings are also in line with studies done in college communities and multicentre areas, which revealed a negative association between the detection of aerosolized IAV and the time elapsed since illness onset [ 51 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Varying clinical presentations and virus shedding rates have been correlated with numbers of influenza virus copies in nasopharyngeal samples. 16,17 In this study, we have shown that virus copies were about two logs higher in the NPS samples of patients with mild disease compared to those with moderate or severe disease, though this was not statistically significant. Thus, disease severity/symptomatology of COVID-19 does not correlate with SARS-CoV2 copies in NPS samples: this may reflect stage in the evolution of disease.…”
Section: Sars-cov2 Primarily Infects Epithelial Cells Lining the Oral Oropharyngeal And Respiratorycontrasting
confidence: 53%
“…Lee et al, 2011;C. C. Li et al, 2010;Loeb et al, 2012;Lu et al, 2012;Meschi et al, 2011;Ngaosuwankul et al, 2010;Rath et al, 2012;Rodrigues Guimaraes Alves et al, 2020;Suess et al, 2010;Thai et al, 2014;To, Chan, et al, 2010;To, Hung, et al, 2010;Watanabe, Nukuzuma, Ito, & Ihara, 2011;Wu, Wang, Chen, & Chang, 2012;Yang, Lo, Ho, Wu, & Liu, 2011) and data were collected from each study. For preprinted studies that were published as journal articles before the revised submission of this manuscript, we included the citation for the journal article.…”
Section: Med and Bmj)mentioning
confidence: 99%